Characterization of the complete mitochondrial genome of a holothurians species: Holothuria hilla (Holothuroidea: Holothuriidae) - Yang, Qiuhua (Mitochondrial DNA B Resour, 2019)
Mitochondrial genome sequence is a great potential method to both resolve disputed taxonomic issues and to infer phylogenetic relationships among holothurians. In this study, we present the complete mitochondrial genome of Holothuria hilla which was 15,744 bp in length, containing 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a putative control region. The gene content and arrangement were typical for Holothuroidea ground pattern. The overall base composition was 32.43% A, 27.20% T, 24.35% C and 16.02% G, showing a bias toward A + T (59.63%). The maximum-likelihood tree based on the concatenated 13 protein-coding genes revealed the phylogenetic relationships among the Holothuroidea species.